The Relationship between Attitude and the Exploitation of Information and Communication Technology in Nursing Students - M Pouralizadeh; K Noruzi; Z Moradian (Iran University of Medical Sciences, 2017)
Abstract Background & Aims: The use of information and communication technology as a modern technology is rapidly expanding in current world and has been known. The aim of this study was to investigate the relationship between nursing students' attitudes and the exploitation of information and communication technologies. Materials & Methods: This was a correlational study conducted using the convenience sampling method. The study participants were 102 undergraduate and postgraduate nursing students from Gilan and Hamedan Universities of Medical Sciences; also School of Rehabilitation affiliated to Tehran University of Medical Sciences. The data collection instrument was a questionnaire by Hosseinzadeh et al. including the use of computer activities, Internet activities, and students' attitudes towards information and communication technology. The data were analyzed by descriptive and inferential statistics using the SPSS software version 16. Results: The assessment of relationship between the use of computer activity, Internet activity and attitude towards information and communication technologies revealed a positive and significant correlation between the use of computer and attitude (r= 0.51, P <0/001). Conclusion: The results of the study indicated a positive correlation between nursing students' attitudes and computer and internet skills. As the major goal of nursing education is professional competency, therefore, similar research is needed for guiding nursing students in using advance scientific technologies. It is suggested that future studies should address facilitators and barriers to Internet use in the pursuit of research and evidence-based practice in the bigger students' and nurses' groups.